DEVELOPING TRANSPORT CORRIDOR KEY ROUTE FOR CENTRAL ASIA (American Journal of Business Management, Economics and Banking, 2024)
This article discusses the creation of a new transport corridor through the Caspian Sea of Turkmenistan and Azerbaijan with Russia, Georgia and Turkey, Uzbekistan and Kyrgyzstan opening up alternative routes for export and import flows. The economic and political objectives of each participating country, the risks and challenges of the project, such as the need for coordination, political and environmental risks, as well as financial and technical difficulties, are analyzed. A conclusion is drawn about the long-term importance of the corridor for the regional economy and geopolitics, prospects for attracting investment, developing infrastructure and strengthening economic stability in Central Asia are outlined.